Quantitative Sørensen–Dice Indexed Damgård–Jurik Cryptosystem For Secured Data Access Control In Cloud. Issue 1 (December 2020) - Calistabebe, P; Akila, D
Abstract: Data Access Control has become a demanding issue in cloud storage systems. Access control is the protection method to control who can view or access the information in computing scenarios. Some techniques have been designed formost of the security strategiesprovidedtotheclients accessingtheuploadeddata. AQuantitative Sørensen–Dice Indexing Damgård–Jurik Cryptosystem based Data Access Control (QSDIDJC-DAC) method is introduced to avoid the illegitimate data access in the cloud server. Initially, the QSDIDJC-DAC method comprises five processes, namely registration, key generation, authentication, encryption and decryption for data access. At first, the clientsregister their information to the cloud server. After that, the cloud server generates the key pairs (i.e., public key, private key). Then the client encrypts the data with the general public key and sends it to the cloud server for storing the data. During the data access, the user transmits the request to the cloud server. Upon receiving the request, the authentication server verifies the cloud user is a legitimate user using the Quantitative Sørensen–Dice similarity coefficient with higher authentication accuracy. The Similarity Coefficient matches the requested user with user information stored in the cloud server on the time of registration. Based on the similarity value, the legitimate and illegitimate users are correctly identified with minimum time consumption. After performing the verification process, the cloud server allows legitimate users to access the data. Subsequently, the client decrypts the data with the help of their private key. This helps to enhance the data access control in the cloud server with a better security level. Experimental assessment is carried out on factors such as authentication accuracy, computation time and data confidentiality rate with recognize to some of the cloud users and thedata.